2008
DOI: 10.1111/j.1574-6941.2007.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of predominantly nonculturable rhizobia with diverse, endophytic bacterial taxa within nodules of wild legumes

Abstract: A previous analysis showed that Gammaproteobacteria could be the sole recoverable bacteria from surface-sterilized nodules of three wild species of Hedysarum. In this study we extended the analysis to eight Mediterranean native, uninoculated legumes never previously investigated regarding their root-nodule microsymbionts. The structural organization of the nodules was studied by light and electron microscopy, and their bacterial occupants were assessed by combined cultural and molecular approaches. On examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 51 publications
5
100
0
2
Order By: Relevance
“…Another study showed that inoculating plants with AM Q:1 fungi changed the bacterial community and improved plant growth most likely because of improved shoot N, P, and K levels (Rodríguez-Caballero et al 2017). Nevertheless, the most commonly isolated members of the legume nodule community outside of rhizobia consist of Grampositive and Gram-negative bacteria, some of which have the capacity to fix N 2 (Aserse et al 2013;Deng et al 2011;Muresu et al 2008).…”
Section: F1mentioning
confidence: 99%
“…Another study showed that inoculating plants with AM Q:1 fungi changed the bacterial community and improved plant growth most likely because of improved shoot N, P, and K levels (Rodríguez-Caballero et al 2017). Nevertheless, the most commonly isolated members of the legume nodule community outside of rhizobia consist of Grampositive and Gram-negative bacteria, some of which have the capacity to fix N 2 (Aserse et al 2013;Deng et al 2011;Muresu et al 2008).…”
Section: F1mentioning
confidence: 99%
“…De Meyer et al / Soil Biology & Biochemistry xxx (2015) 1e11 7 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64The data presented in this study suggest the presence of a large diversity of bacteria belonging to 50 genera inside nodules of indigenous legumes in Flanders. Plants house several endophytes within their tissues and multiple studies have reported the presence of endophytes in legumes (Muresu et al, 2008;Ibañez et al, 2009;Muresu et al, 2010). One of the genera in our study, Phyllobacterium (Table 1) is a known nodule endosymbiont and is capable of fixing nitrogen (Valverde et al, 2005;Baimiev et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…This incapacity may occur due to the loss of plasmids that carry the symbiotic genes during the successive cultivations in the process of isolation, purification and storage (Garcia de los Santos, 1996). For tree species, isolation of nonsymbiotic bacteria that co-inhabit the nodules, together with the rhizobia may also occur, as is described in the literature (Muresu et al, 2008;Shiairashi et al, 2010). These non-symbiotic organisms, because they take less time to appear in culture medium, occupy the Petri dishes more rapidly, which does not permit the observation of isolates that appear lately (Ourarhi et al, 2011).…”
Section: Discussionmentioning
confidence: 91%